Do you think medicines can be prescribed in a more eco-directed, greener way? A qualitative study based on public and prescriber focus groups on the impact of pharmaceuticals in Scotland’s water environment - Claire Anderson; Lydia Niemi; Naoko Arakawa; Mark Taggart; Stuart Gibb; Sharon Pfleger (BMJ Open)
Objectives This qualitative study explored public and prescriber awareness of pharmaceutical pollution in the water environment and eco-directed sustainable prescribing (EDSP) as a mitigation strategy to reduce the environmental impact of prescribing in Scotland.Design Focus groups explored prescriber and public perceptions of the topic. Common questions were asked through semistructured facilitation. Focus groups were digitally recorded and transcribed verbatim using an artificial intelligence system, then anonymised and thematically analysed using NVivo software. Data were iteratively analysed using the one sheet of paper technique.Setting Public focus groups were held in-person (Inverness, Scotland, April 2023), and prescriber focus groups were held virtually (MS Teams, August 2023).Participants Nine public representatives and 17 NHS Scotland prescribers participated in one of four focus groups. Purposive and opportunistic sampling approaches were used to recruit participants through social media and other channels (ie, community groups, professional emails, general practitioner and hospital flyers). Prescriber representatives registered interest through an online survey to gather information about their professional background. Responses were reviewed to ensure representation of a mixture of medical backgrounds, experience, sectors and health boards.Results There is growing awareness among the public and healthcare professionals of pharmaceutical pollution in the environment, but further education is required on the drivers, potential effects and possible interventions. Suggestions for more sustainable healthcare included public health awareness campaigns, better provision for pharmacy take-back schemes, clear medicine/packaging labelling, regular medicines reviews and more considered patient-centred care. From the prescriber perspective, EDSP resonated well with current sustainability initiatives (eg, Realistic Medicine, switching to dry-powder inhalers), but barriers to EDSP included lack of knowledge, confidence, time and resources to implement changes. Although the public representatives were generally open to the concept of EDSP, this decision required weighing pros/cons considering personal health choices, information accessibility and transparency, and trust in and time with prescribers.Conclusions This study identified new insights from prescribers and the public related to the concept of, and barriers to, EDSP in Scotland, as well as perspectives regarding knowledge support tools and information communication. Cross-sector and transdisciplinary collaborative approaches are needed to address the challenges identified here. Nonetheless, EDSP merits further exploration in developing more sustainable, appropriate and effective healthcare which contributes to improved public and planetary health.